Pottery production, exchange and consumption in Late Bronze Age Magnesia (Thessaly): results of neutron activation analysis of pottery from Dimini, Volos (Nea Ionia, Kastro/Palaia), Pefkakia and Velestino - Lis, Bartłomiej; Mpatziu-Eustathiu, Anthē; Adrymi-Sismani, Vassiliki; Mommsen, Hans; Maran, Joseph; Prillwitz, Susanne (The annual of the British School at Athens, 2023)
This article presents the results of Neutron Activation Analysis (NAA) of, altogether, 145 pottery and clay samples deriving from five sites located in the Thessalian region of Magnesia: Dimini, Nea Ionia, Kastro/Palaia (Volos), Pefkakia and Velestino. Chronologically, the sampled pottery covers the entire Late Bronze Age (LBA), with a few samples dating to the Middle Bronze Age. Within this broad chronological range, Mycenaean-type pottery dominates, the majority of it being decorated, with an addition of fine unpainted pottery and such used for transport and cooking. Pottery of non-Mycenaean derivation is represented by a variety of types belonging to the early LBA as well as two classes of the early post-palatial period (i.e. after 1200 BC): Handmade Burnished Ware and Grey Ware. Importantly, samples associated with two pottery kilns at Dimini and Velestino were included in the project, although no kiln wasters were identified. Results of the analysis provide important insights into both local Thessalian pottery production and inter- and intra-regional pottery exchange. Local production utilising clay beds around Dimini is best evidenced, with a distribution of its products reaching beyond Thessaly. Two further chemical patterns appear to be associated with Velestino, while an additional two small chemical groups are likely Thessalian as well. In terms of identified imports, the Argolid stands out as the major source of non-local pottery from the beginning of the LBA until the end of the palatial period. Other regions and production localities play a significantly smaller role as sources of supply. On the basis of the study, for the first time the local production as well as importation of pottery in the region of Magnesia is documented by scientific means, opening new research perspectives and strengthening the region's standing as part of the Mycenaean world